2011
DOI: 10.1021/ja206380h
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Na-doped PbTe–PbS Thermoelectric Materials: Electronic Density of States Modification and Shape-Controlled Nanostructures

Abstract: Thermoelectric heat-to-power generation is an attractive option for robust and environmentally friendly renewable energy production. Historically, the performance of thermoelectric materials has been limited by low efficiencies, related to the thermoelectric figure-of-merit ZT. Nanostructuring thermoelectric materials have shown to enhance ZT primarily via increasing phonon scattering, beneficially reducing lattice thermal conductivity. Conversely, density-of-states (DOS) engineering has also enhanced electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
264
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(294 citation statements)
references
References 45 publications
20
264
3
2
Order By: Relevance
“…The high thermoelectric performance of solid solution quaternary Pb-Te-Se-S alloys can potentially start a new research direction in Pb-chalcogenides, based on adjusting the band gap and the energy separation between the upper and the lower valence bands to enhance the Seebeck coefficient, where low thermal conductivity is guaranteed due to scattering of long wavelength phonons at point defects. Comparison of the thermoelectric efficiency of the quaternary system in the present study with maximum reported values for binary p-type PbSe, 32 p-type strontium-added PbS, 40 strontium-added PbTe 6 and p-type PbTe-12 at% PbS 19 and PbTe-16 at% PbS, 19 indicating larger efficiency over a wide temperature range.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The high thermoelectric performance of solid solution quaternary Pb-Te-Se-S alloys can potentially start a new research direction in Pb-chalcogenides, based on adjusting the band gap and the energy separation between the upper and the lower valence bands to enhance the Seebeck coefficient, where low thermal conductivity is guaranteed due to scattering of long wavelength phonons at point defects. Comparison of the thermoelectric efficiency of the quaternary system in the present study with maximum reported values for binary p-type PbSe, 32 p-type strontium-added PbS, 40 strontium-added PbTe 6 and p-type PbTe-12 at% PbS 19 and PbTe-16 at% PbS, 19 indicating larger efficiency over a wide temperature range.…”
Section: Discussionsupporting
confidence: 53%
“…[13][14][15][16] Ternary PbTe-rich alloys of PbTe-PbSe 4,17,18 show a higher figure of merit than individual binary PbTe and PbSe systems in the temperature range of 550-800 K, mainly due to alteration of the electronic band structure. 4,18 In contrast, higher zT values of PbTe-PbS [19][20][21][22] compared to the binary systems are credited to the reduction in lattice thermal conductivity, which originates from phonon scattering at the interfaces of secondary phases, as PbS shows very limited solubility in the PbTe matrix. 23 Here, we present a strategy to design single-phase quaternary alloys with high thermoelectric efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult, however, to concurrently improve all of the parameters because these three parameters are interrelated by carrier concentration. Recently, several strategies and concepts indicated that higher ZT values could be obtained in nanomaterials by a tailoring of the band structure and the phonon scattering [5][6][7][8][9][10][11]. Therefore, the pursuit of different TE materials using low-dimensional systems has recently become an active research field.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of nanostructures into bulk thermoelectric materials gives the opportunity to independently tune these parameters [7,8] and significantly reduces the thermal conductivity by scattering a broad spectrum of phonons. [9,10] Recently, band engineering based on modifying the band structure by alloying [11][12][13] or doping to create impurity levels for resonating with the host band [14,15] or both [16,17] lead to significant achievements in obtaining higher ZT values.…”
Section: Introductionmentioning
confidence: 99%